Cloning of the filamentous hemagglutinin of Bordetella pertussis and its expression in Escherichia coli. - Brown, D R (1987)
Bordetella pertussis UT25 DNA was cloned into the kanamycin resistance gene of cosmid pCP13 to construct a genomic library in Escherichia coli LE392. One clone containing plasmid pDB441 expressed the filamentous hemagglutinin (FHA) as identified by protein immunoblots with the use of rabbit anti-B. pertussis antiserum, rabbit anti-FHA antiserum, and a monoclonal antibody to FHA. FHA is a protein of 220 to 210 kilodaltons, but the immunoreactive FHA, as expressed in E. coli, was larger than that expressed in B. pertussis, suggesting that there was a difference in the processing of this protein between these two bacteria. The fha gene was mapped to a 6.5-kilobase pair DNA fragment by the use of various restriction endonucleases. The kanamycin resistance gene of pCP13 was found to provide the promoter function but probably not the translation start signal for the fha gene. Conjugative transfer of pDB441 to B. pertussis BP353, a transposon Tn5-induced FHA mutant, increased the expression of the FHA over that seen with wild-type B. pertussis.